Pain and Fatigue in Elderly Cancer Patients Turkey Example - Erturk, Melek; Yildirim, Yasemin; Kilic, Serap Parlar; Ozer, Serap; Aykar, Fisun Senuzun (Lippincott Williams & Wilkins, 2015)
The aim of this study was to evaluate the pain and fatigue levels of elderly cancer patients and to examine whether pain is an independent variable in fatigue development. A total of 250 elderly cancer patients undergoing treatment in the outpatient chemotherapy units and internal medicine clinic at 2 hospitals were enrolled. A Patient Information Form, the McGill Melzack Pain Questionnaire, and the Brief Fatigue Inventory were used as data instruments. It was determined that all patients had pain and that the mean present pain intensity score was 2.70 +/- 0.99, the mean worst pain intensity score was 4.40 +/- 0.86, and the mean least pain intensity score was 1.40 +/- 0.66. Whereas the existing fatigue severity score of the patients with fatigue (43.6%) was 6.27 +/- 2.06, the mean usual fatigue severity of the patients in the last 24 hours was 6.19 +/- 1.63 and that the mean worst fatigue severity score in the last 24 hours was 7.29 +/- 1.57. When the regression analysis carried out between the pain and fatigue intensities is examined, it was determined that pain is an independent variable in increasing fatigue and that there is a statistically significant relationship (P <.05). It is important that nurses develop strategies to prevent and determine activities to decrease the pain and fatigue of the patients while planning and implementing their holistic care in a relevant manner.
Keywords: cancer; elderly; fatigue; pain; Turkey